Implementasi Fatwa DSN-MUI tentang penjualan Langsung Berjenjang Syariah No.75/VII/2009 pada PT Herbal Amanah Impian Indonesia - Jundana, Qonita; Hermawan, Aries (Journal of Fiqh in Contemporary Financial Transactions, 2024)
This research aims to analyze the multilevel marketing business practices of PT Herbal Amanah Impian Indonesia (HAII) and business implementation based on fatwa No.75/DSN-MUI/VII/2009. Qualitative research methods using field research methods by comparing between field implementation and sharia conformity regulated in fatwa No.75/DSN-MUI/VII/2009. The results of this study indicate that the company's multilevel marketing business practices are carried out according to the standardization that has been determined from the various certifications obtained. Judging from fatwa No.75/DSN-MUI/VII/2009, the practices carried out by PT Herbal Amanah Impian Indonesia based on the business plan system, products, and bonus/rewarding system, are in accordance with the standardization of the fatwa, so that the business implementation is categorized as fulfilling the elements of sharia multilevel direct sales.